Andreev reflection study of the new magnetic superconductor M₃Sb₇: evidence for the gap anisotropy - Dmitriev, V.M.; Rybaltchenko, l.F.; Khristenko, E.V.; Ishchenko, l.A.; Bukowski, Z.; Troć, R. (Физика низких температур, 2007)
We report the point-contact (PC) Andreev-reflection experiments on the new paramagnetic superconductor Mo₃Sb₇ for which we have observed strong distinctions in the PC spectra measured for different contact axis orientations. Analysis of the PC spectra in the framework of the Blonder—Tinkham—Klapwijk theory has shown that the gap parameter is strongly anisotropic varying over a very wide range depending on the contact orientation when the maximum max can exceed at least 40 times the minimum min. For these and other reasons we suggest that Mo₃Sb₇ is not a trivial BCS (s-wave) superconductor but rather has a (s+g )-wave or another unconventional pairing symmetry.